A survey of the dentist attire and gender preferences in dentally anxious children - Alexander Asokan; Haalaswamy V Kambalimath; Raju U Patil; Sathish Maran; K P Bharath (Wolters Kluwer Medknow Publications, 2016)
Background: Anxiety about doctors among children is very common. White coat phobia which is a classical conditioning phenomenon is said to be prevalent among children. Objectives: To analyze the association between anxious states of children about dentists and their preference of dentist attire and gender in the dental office. Materials and Methods: The 9-12-year-old middle school children were selected for the study. Children were asked to fill a questionnaire containing children's fear survey schedule-dental subscale (CFSS-DS) and asked to prefer dental attire from four different pictures displaying the single anonymous dentist in four different attires in the same operator. The CFSS-DS gave the anxiety scale, and age, gender, and experience were also plotted against children preference in an apron, protective wear, and gender preference. Results were tabulated and statistically analyzed using Chi-square test. Results: About 718 (62%) were scored as anxious children. Of all anxious children, 502 (69.9%) had preference of colored attires of the dentist, and 408 (66.8%) anxious children preferred dentist with protective wear. Female dentists were preferred by 452 (66%) anxious children. Same gender preference was also prevalent.